2012
DOI: 10.1111/j.1475-682x.2012.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Collective Efficacy and Crime in Los Angeles Neighborhoods: Implications for the Latino Paradox*

Abstract: We use data from the Los Angeles Family and Neighborhood Study (LAFANS) to examine the degree to which social ties and collective efficacy influence neighborhood levels of crime, net of neighborhood structural characteristics. Results indicate that residential instability and collective efficacy were each associated with lower log odds of robbery victimization, while social ties had a positive effect on robbery victimization. Further, collective efficacy mediated 77 percent of the association between concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 46 publications
4
51
1
Order By: Relevance
“…They found in their research that when community residents in urban areas do not have adequate social networks built on trust and reciprocity that both violent and property crimes are higher than they otherwise would be. This finding fits well with what other researchers have found regarding social capital and social control, urban crime and routine activities, rail transit, and cultural assimilation (Browning, Calder, Boettner, & Smith, 2017;Burchfield & Silver, 2013;MacDonald, Hipp, & Gill, 2012;Ridgeway & MacDonald, 2016). Burchfield and Silver (2013) found in their research on Latino Los Angeles residents that the more social disorganization there is in the community the more likely they are to be victimized and the higher overall crime rates are.…”
Section: Literature Reviewsupporting
confidence: 79%
See 3 more Smart Citations
“…They found in their research that when community residents in urban areas do not have adequate social networks built on trust and reciprocity that both violent and property crimes are higher than they otherwise would be. This finding fits well with what other researchers have found regarding social capital and social control, urban crime and routine activities, rail transit, and cultural assimilation (Browning, Calder, Boettner, & Smith, 2017;Burchfield & Silver, 2013;MacDonald, Hipp, & Gill, 2012;Ridgeway & MacDonald, 2016). Burchfield and Silver (2013) found in their research on Latino Los Angeles residents that the more social disorganization there is in the community the more likely they are to be victimized and the higher overall crime rates are.…”
Section: Literature Reviewsupporting
confidence: 79%
“…It is widely believed in the general population that the higher the immigration rates the higher the crime rates, but many studies have not found this to be the case. It is not immigration per se that is associated with crime, it has more to do with matters pertaining to poverty, social capital, routines activities, the transitional nature of communities, social disorganization, and so forth (Browning et al, 2017;Burchfield & Silver, 2013;Chang & Lau, 2016;Ridgeway & MacDonald, 2016). Macdonald et al (2013) found that the higher the levels of assimilation among immigrants the lower the crime rates are in any given area.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Fear of crime can stimulate and accelerate neighborhood decline by encouraging residents to withdraw physically and psychologically from community life, resulting in a commensurate decline in a neighborhood's social capital (Skogan, 1986). On the other hand, as social capital in these neighborhoods increases, violent crime is likely to decrease in these neighborhoods (Burchfield & Silver, 2013).…”
Section: Crime and Public Safetymentioning
confidence: 99%